Download presentation

Presentation is loading. Please wait.

Published byTeresa Jackson Modified over 5 years ago

1
To prove by induction that (1 + x) n ≥ 1 + nx for x > -1, n N Next (c) Project Maths Development Team 2011 Note: x>-1. Hence (1+x)>0.

2
Prove: (1 + x) n ≥ 1 + nx for n=1 For n = 1 (1 + x) 1 = 1 + x True for n = 1 To prove by induction that (1 + x) n ≥ 1 + nx for x > -1, n N Next (c) Project Maths Development Team 2011

3
Assume true for n = k. Therefore (1 + x) k ≥ 1 + kx Multiply each side by 1 + x (1 + x)(1 + x) k ≥ (1 + x)(1 + kx) (1 + x) k+1 ≥ 1 + kx + x + kx 2 Since (1 + x) k+1 ≥ 1 + kx + x + kx 2 (k > 0 then kx 2 ≥0 for all x) Therefore (1 + x) k+1 ≥ 1 + kx + x (1 + x) k+1 ≥ 1 + (k+1)x If true for n = k this implies it is true for n = k + 1. It is true n = 1. Hence by induction (1 + x) n ≥ 1 + nx x > -1, n N. To prove by induction that (1 + x) n ≥ 1 + nx for x > -1, n N (c) Project Maths Development Team 2011 Prove true for n = k + 1

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google